The Neglect of Husband’s Nusyuz in Indonesian Islamic Civil Law: A Doctrinal Analysis of Qur’anic Principles and the Compilation of Islamic Law - Nur Wahid, Ahmad (Berasan: Journal of Islamic Civil Law, 2025)
The study aims to examine the concept of husband’s nusyuz within Islamic civil law and to evaluate its absence in the Indonesian Compilation of Islamic Law (KHI). Although the Qur’an, particularly Surah An-Nisa (128), recognizes the possibility of marital disobedience by husbands, the KHI explicitly regulates only the wife’s nusyuz, thereby creating a doctrinal imbalance. Employing a normative juridical method with a doctrinal and analytical approach, this research investigates primary legal sources (the Qur’an and classical fiqh) and positive legal instruments (KHI and related legislation) to identify the normative gap. The findings show that husband’s nusyuz encompasses both material violations, such as the neglect of maintenance and dowry, and non-material violations, including mistreatment, injustice, or abandonment. The omission of husband’s nusyuz in KHI restricts legal remedies available to wives and perpetuates asymmetry in marital rights and obligations. The study concludes that doctrinal reform is required to incorporate explicit provisions on husband’s nusyuz into KHI, thereby harmonizing Indonesian Islamic civil law with Qur’anic principles and the objectives of maqāṣid al-sharī‘ah. Such reform would strengthen legal protection for wives and promote greater gender justice within the framework of Islamic family law in Indonesia.